Contribution of lianas to plant area index and canopy structure in a Panamanian forest. Issue 12 (2nd December 2016) - Rodríguez‐Ronderos, M. Elizabeth; Bohrer, Gil; Sanchez‐Azofeifa, Arturo; Powers, Jennifer S.; Schnitzer, Stefan A.
Abstract: Lianas are an important component of tropical forests, where they reduce tree growth, fecundity, and survival. Competition for light from lianas may be intense; however, the amount of light that lianas intercept is poorly understood. We used a large‐scale liana‐removal experiment to quantify light interception by lianas in a Panamanian secondary forest. We measured the change in plant area index (PAI) and forest structure before and after cutting lianas (for 4 yr) in eight 80 m × 80 m plots and eight control plots (16 plots total). We used ground‐based LiDAR to measure the 3‐dimensional canopy structure before cutting lianas, and then annually for 2 yr afterwards. Six weeks after cutting lianas, mean plot PAI was 20% higher in control vs. liana removal plots. One yr after cutting lianas, mean plot PAI was 17% higher in control plots. The differences between treatments diminished significantly 2 yr after liana cutting and, after 4 yr, trees had fully compensated for liana removal. Ground‐based LiDAR revealed that lianas attenuated light in the upper‐ and middle‐forest canopy layers, and not only in the upper canopy as was previously suspected. Thus, lianas compete with trees by intercepting light in the upper‐ and mid‐canopy of this forest.